PEMEROLEHAN BAHASA ANAK: KAJIAN ASPEK FONOLOGI PADA ANAK USIA 2 - 2,5 TAHUN - Prima Gusti Yanti (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2016)
This article aims to explain child language acquisition 2–2.5 years of age phonological aspects which include the acquisition of vowels, consonants, and factors affecting the phonological acquisition. The research was conducted in Jakarta from August 2011 through February 2012 .The method used in this research was qualitative method with case study approach. Sources of data were obtained from TPM and these data were collected during six months of observation, diaries, and interviews. The findings in this article shows that TPM has mastered the phoneme [a], [i], [u], [e], [o], [âˆ‚], [Ñ”], and [ÎŸ]. Vowel phonemes was mastered at the age of 2 years and 1 month. The first vowel that it controls is a vowel [a], [i] and [u], then the front vowel [i], [e], [Îµ], and then back vowel [u], [o], [ ×›], and vowel [âˆ‚], [a]. Double vowel sound that is not a diphthong also been mastered by the age of 2 years and 3 months, for example, [au], [ai] and [ue]. However, the original diphthong [au] and [ai] recently mastered at age 2 years and 6 months. Meanwhile, the consonant [p], [b], [t], [d], [s], [h], [c], [j], [m], [n], [Å‹], [l ], [w] and [y] mastered well. Consonant [t], [s], [c], [j] and [Å‹] has appeared, but still fluctuates with another sound. The sound resistor velar [g] and [k] are not pronounced properly. The sound [k] is mastered if located in the middle and end of words. Sound fricative [f] and [v] and trill [r] has not yet emerged and mastered. TPM perform substitution pattern to pronounce phonemes had not conquered, such as phonemes [f], [v], [z], and [x]. The appearance of a wide range of variation in her phonological acquisition largely is caused by the incomplete of her speech organ. Research is still open for further research the acquisition of phonology because language acquisition TPM has yet to reach the Summit. But it can also examine language acquisition on aspects of other languages.